The Late Saalian Cyprina clay of northeastern Germany and the following Weichselian sedimentation and deformation history – Review and new data. (2nd June 2020) - Obst, Karsten; Ansorge, Jörg; Thiel, Christine; Frenzel, Peter
Abstract : Glacially dislocated fossiliferous clay – hitherto called Cyprina clay– and associated Pleistocene sediments are exposed at the northeastern German coast. They were uplifted as glacial rafts from a position of about 30 m below the sea level and incorporated into glaciotectonic complexes of Dornbusch (Hiddensee), Arkona (Rügen) and Greifswalder Oie during the ice advances of the Last Glacial Maximum (LGM). Optically stimulated luminescence (OSL) ages of the fossil‐bearing clay and the overlying glacifluvial/lacustrine successions give insights into Late Saalian, Eemian and Early to Middle Weichselian development of the southern Baltic Sea area. The age data especially support the observation of changing environmental conditions prior to the Eemian warm period as suggested by the fossil record. A high‐arctic brackish fauna documented in a lower reddish‐grey clay is followed by a more boreal brackish‐marine to marine fauna in the overlying olive and/or greenish‐grey clay. This implies conditions of glacial meltwater running to the northwest during the deglaciation phase of the last Saalian Warthe ice advance and inflow of cold marine water from the North Atlantic area along the margin of the Scandinavian Ice Sheet into the Skagerrak and the Kattegat. Subsequently, water with higher salinity entered the mouths and channels of large rivers crossing the southern Baltic Sea area from SE to NW comparable with those of the Oder and Vistula rivers. Eemian Cyprina clay deposits with lusitanian faunal elements are not exposed in the study area but occur in Denmark and northwestern Germany. To distinguish the different facies types and age of the clay, we introduce the stratigraphical term Vitt Formation for the Late Saalian Cyprina clay in NE Germany, comprising Roundstonia, Portlandia and Arctica members – each with characteristic microfossil species.